Study of Family Behavior that At Risk For Pneumonia in Under Five Children in Mempawah District - Meilantika, Ayu Diana; Hadisaputro, Suharyo; Mexitalia, Maria; Rahardjani, Kamilah Budhi; Sakundarno, Mateus (Health Notions, 2018)
Pneumonia is respiratory infection disease which effects lungs and there are many cases on under five children. Prevalence period of pneumonia case in Mempawah district the fourth highest of 3.6% of other districts. The purpose of this study was to prove family behavior that are risk of pneumonia in under five children in Mempawah district. This study used case control design. Subject of the study was 100 respondents which consisted of 50 cases and 50 controls meeting the criteria of inclusion. This research use consecutive sampling techniques. Data analysis uses logistic regression. Data were analysed by logistic regression method. Result of analysis shows that history of not exclusive breastfeeding (OR=11.391; 95%CI: 3.087-42.028), habits of not opening room windows (OR= 9.528; 95%CI: 2.699-33.640), existence of pets (OR= 7.871; 95%CI: 2.381-26.019) dwelling density (OR=6.623; 95%CI=1.770-24.785) are proven as risk factors of pneumonia in under five children. Family behaviors as history of not exclusive breastfeeding, habits of not opening room windows, existence of pets, and dwelling density are proven as risk factors of pneumonia in under five children. Keywords: Family behavior, Pneumonia, Under five children